Фізико-хімічні процеси у виливках при зносостійкому легуванні поверхні - Ковальчук, О.Г.; Ямшинський, М.М.; Федоров, Г.Є. (Physico-technological Institute of Metals and Alloys, 2023)
The authors investigated the processes of surface alloying with the use of ferroalloys, which include carbide-forming elements. Such studies gave positive results and confirmed the usefulness of applying ferromanganese and ferrochrome as fillers for alloying coatings. Surface alloying can significantly increase the wear resistance of castings as a result of controlling the processes of structure formation in the surface layer. In order to achieve an alloyed layer of the required thickness, ferroalloys may be promising, the melting points of which are as close as possible to the temperatures of the melt poured into the mold or below. The best and cheapest materials for producing castings with differentiated surface properties are powders of ferroalloys or their mechanical mixtures. To achieve high surface hardness and wear resistance of cast parts, methods of producing castings from unalloyed iron-based melts with a surface composite or alloyed layer formed during the formation of a casting in a mold can have a perspective. The granulometric composition of alloying coating significantly affects the thickness of the alloyed layer and it is chosen depending on the melting temperature of the coating and the possible overheating of the base metal before pouring it into the mold.